DETECTING TRANSOVARIAL INFECTION IN AEDES AEGYPTI BASED ON IMMUNOCYTOCHEMICAL STREPTAVIDIN BIOTIN PEROXIDASE COMPLEX ASSAY (ISBPC) IN BALI - Purnama, Sang Gede (Journal of Health Sciences and Medicine, 2018)
Immunocytochemical method is one of dengue virus examination alternative with affordable cost. Through immunocytochemical methods it will be proven that transovarial transmission of dengue virus from mosquitoes to their eggs and its relationship with the incidence of DHF in Bali. This study is done by the installationovitrap indoor and outdoor as much as 1200 points. The mosquito will be cultured for dengue virus examination using the Immunocytochemical-Immunomodoxidase streptavidin biotin complex (IISBC) method of head squash. The results of examination of larvae density were known to the ovitrap index in Denpasar (4.4), Tabanan (6.6), Gianyar (8.9). There is evidence of transovarial transmission from female mosquitoes to eggs using Immunocytochemical Technique known to its transovarial index of each city ie Denpasar (11%), Gianyar (7.14%) and Tabanan (7.14%). Key words: transovarial, immunocytochemical, Bali